ANALYSIS OF BEHAVIOR AND SELF-CONTROL ON STUDENTS' ENTREPRENEURIAL MOTIVATION AT STMB MULTI SMART - Mario Andrias Kiton; Ferry Hidayat; Sere Theresia Yohana Aruan (RADJA PUBLIKA, 2025)
This study aims to determine the effect of behavior and self-control on entrepreneurial motivation of students at STMB Multi Smart Medan. The research method used is descriptive quantitative with a statistical approach to test the effect of behavioral variables and self-control on entrepreneurial motivation. The study population was all students of the Business Administration, Management, and Accounting Study Programs for the 2021-2024 period totaling 315 students, with a sample of 76 students taken using the Slovin formula sampling technique with a margin of error of 10%. Data were collected through a Likert scale questionnaire and analyzed using the SPSS program. Analysis techniques include validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that partially behavior has a positive and significant effect on entrepreneurial motivation of students. Likewise, self-control partially has a positive and significant effect on entrepreneurial motivation. Simultaneously, behavior and self-control have a positive and significant effect on entrepreneurial motivation of students at STMB Multi Smart Medan. These findings indicate the importance of developing behavior and self-control in increasing entrepreneurial motivation of students.